RELIGIOSITAS PADA PENGIKUT PAGUYUBAN NGESTI TUNGGAL - Melati Dwi Lestari; Fina Rahmawati (Academica: Journal of Multidisciplinary Studies, 2020)
This research was conducted to find out how many followers of the Paguyuban Ngesti Tunggal believe in the existence of religion or just as a formality, and also to find out the flow of someone who follows the Paguyuban Ngesti Tunggal. The method that I use in this research is by interviewing direct respondents who are competent in the field of paguyuban Ngesti Tunggal. The conclusions are of followers of the Paguyuban Ngesti Tunggal are that the followers of the Paguyuban Ngesti Tunggal are their own uniqueness where Pangestu is a pure organization, not a group of followers of belief or religion. Therefore, Pangestu members carry out worship in accordance with their respective teachings. The Pangestu association is also an organization whose members are required to balance the relationship between humans and their God as well as humans and humans.Keyword:Â Pangestu; Religiosity; Stream of worshipers